Inequality, Just Price and Bad Bargains: Contracting Attitudes after the South Sea Crash, 1720. Issue 3 (2nd September 2019) - Bogle, Stephen
ABSTRACT: In 1720, following the crash in South Sea stock, some doubted the legal and ethical enforceability of contracts concluded on the secondary market for the purchase of future South Sea stock. This article examines the argument of David Dalrymple who drew upon civil law, natural law and the notion of a just price to advocate for the annulment of these so called 'time bargains'. It demonstrates why Dalrymple's just price argument held a rhetorical relevance, as an ethical argument, even if the effectiveness of such a plea in both Scottish and English courts, during the early eighteenth century, is doubtful. Additionally, in setting out the context of his pamphlet and the wider debate, this article also draws attention to the emergence of a new ethical rhetoric of commerce and contracting, which argued against Dalrymple, and for the enforcement of these contracts. Lastly, this article contends that a wider conception of what constitutes the legal context of the South Sea crisis is needed, through which a deeper understanding can be gained of what role the law played in resolving the crisis and how political and ethical attitudes shaped the use of law, specifically contract law.